Regulation of CTLA‐4 recycling by LRBA and Rab11. Issue 1 (6th June 2021) - Janman, Daniel; Hinze, Claudia; Kennedy, Alan; Halliday, Neil; Waters, Erin; Williams, Cayman; Rowshanravan, Behzad; Hou, Tie Zheng; Minogue, Shane; Qureshi, Omar S.; Sansom, David M.
Abstract: CTLA‐4 is an essential regulator of T‐cell immune responses whose intracellular trafficking is a hallmark of its expression. Defects in CTLA‐4 trafficking due to LRBA deficiency cause profound autoimmunity in humans. CTLA‐4 rapidly internalizes via a clathrin‐dependent pathway followed by poorly characterized recycling and degradation fates. Here, we explore the impact of manipulating Rab GTPases and LRBA on CTLA‐4 expression to determine how these proteins affect CTLA‐4 trafficking. We observe that CTLA‐4 is distributed across several compartments marked by Rab5, Rab7 and Rab11 in both HeLa and Jurkat cells. Dominant negative (DN) inhibition of Rab5 resulted in increased surface CTLA‐4 expression and reduced internalization and degradation. We also observed that constitutively active (CA) Rab11 increased, whereas DN Rab11 decreased CTLA‐4 surface expression via an impact on CTLA‐4 recycling, indicating CTLA‐4 shares similarities with other recycling receptors such as EGFR. Additionally, we studied the impact of manipulating both LRBA and Rab11 on CTLA‐4 trafficking. In Jurkat cells, LRBA deficiency was associated with markedly impaired CTLA‐4 recycling and increased degradation that could not be corrected by expressing CA Rab11. Moreover LRBA deficiency reduced CTLA‐4 colocalization with Rab11, suggesting that LRBA is upstream of Rab11. These results show that LRBA is required for effective CTLA‐4 recycling by delivering CTLA‐4 to Rab11 recycling compartments, and in its absence, CTLA‐4 fails to recycle and undergoes degradation. Abstract : Correct trafficking of CTLA‐4 is required for its function and mutations in proteins such as LRBA lead to CTLA‐4 deficiency disorders. Here we detail the intracellular pathways involved in CTLA‐4 trafficking using constitutively active and dominant negative Rab GTPases to probe the relationship between CTLA‐4 and LRBA. Our data show CTLA‐4 recycling is strongly dependent on Rab11 activity and that LRBA function is likely upstream of Rab11.